2000
DOI: 10.1257/jep.14.3.75
|View full text |Cite
|
Sign up to set email alerts
|

The Sports Business as a Labor Market Laboratory

Abstract: Professional sports offers a unique opportunity for labor market research. There is no research setting other than sports where we know the name, face, and life history of every production worker and supervisor in the industry. Total compensation packages and performance statistics for each individual are widely available, and we have a complete data set of worker-employer matches over the career of each production worker and supervisor in the industry. These statistics are much more detailed and accurate than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
216
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(232 citation statements)
references
References 38 publications
(3 reference statements)
2
216
3
4
Order By: Relevance
“…It should be noted that this finding is in conflict with the results of extant studies identifying no relationship between pay and performance of elite sport coaches (Frick & Simmons, 2008;Kahn, 2006;Smart et al, 2008). These studies, however, differ from the current study in that they examined the effect of performance on coaching compensation at professional sport settings, such as the National Basketball Association (NBA; Kahn, 2000), Major League Baseball (MLB; Smart et al, 2000), and Bundesliga (Frick & Simmons, 2008). In contrast, this study as well as Humphreys (2000) and Brook and Foster (2010), the other two studies finding a positive relationship between pay and performance, tested this relationship at college sport settings.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…It should be noted that this finding is in conflict with the results of extant studies identifying no relationship between pay and performance of elite sport coaches (Frick & Simmons, 2008;Kahn, 2006;Smart et al, 2008). These studies, however, differ from the current study in that they examined the effect of performance on coaching compensation at professional sport settings, such as the National Basketball Association (NBA; Kahn, 2000), Major League Baseball (MLB; Smart et al, 2000), and Bundesliga (Frick & Simmons, 2008). In contrast, this study as well as Humphreys (2000) and Brook and Foster (2010), the other two studies finding a positive relationship between pay and performance, tested this relationship at college sport settings.…”
Section: Discussioncontrasting
confidence: 92%
“…Along with addressing an important and timely research question, the results of the current research can contribute to the literature by testing the effects of performance and human capital on managerial compensation in an ideal context where (1) individual performance can be clearly defined in terms of wins and (2) detailed data on compensation, performance and human capital characteristics are available to the public (Bloom, 1999;Frick & Simmons, 2008;Kahn, 2000;Smart, Winfree, & Wolfe, 2008;Smart & Wolfe, 2003;Wolfe et al, 2005). Moreover, the results of this study can advance the literature on managerial compensation by providing some of the first empirical evidence regarding the effect of managerial power on the structure of pay.…”
Section: Roles Of Performance and Human Capital In College Football Cmentioning
confidence: 99%
“…Holzer & Ihlanfeldt (1998) show that firms with white clientele are less likely to hire black workers. Additional research has found evidence of customer discrimination, in the form of attendance, television ratings, or other metrics, in the market for sports entertainment (Kahn & Sherer, 1988;Nardinelli & Simon, 1990;Hanssen & Andersen, 1999;Kanazawa & Funk, 2001; see Kahn, 2000 andKahn, 1991 for literature reviews). Evidence of own-race preferences and firm responses to these preferences has been shown in the markets for radio broadcasts (Waldfogel, 2003a), newspapers (George & Waldfogel, 2003) and television broadcasts (Waldfogel, 2003b).…”
Section: Do People Value Racial Diversity? Evidence From Nielsen Ratimentioning
confidence: 99%
“…2 The rich datasets available for professional sports have been noticed by economists, and a significant number of papers have conducted empirical economic analyses using such datasets. See, e.g., Hausman and Leonard (1997), Kahn (2000), Chiappori et al (2002), Duggan and Levitt (2002), Garicano et al (2005), Romer (2006), Price and Wolfers (2010), Parson et al (2011), Abramitzky et al (2012) and Kahane et al (2013).…”
Section: Introductionmentioning
confidence: 99%